The British tradition of minority government - Peacock, Timothy (Book collections on Project MUSE., 2018)
This volume gives a fresh perspective on minority governance using declassified files which challenge some of the myths surrounding the minority administrations in the 1970s, and reveals a British tradition of minority government which goes beyond that of other countries. Conservative plans for a coalition government, a snap General Election, prime ministers considering whether to resign after an electoral or referendum defeat, and the prospect of Labour and Conservative deals with the Liberals, SNP and Northern Ireland Unionist parties, have become dominant features of British politics since 2010, and the hung parliament in June 2017. However, 1970s British political leaders created secret plans for all these scenarios. Using declassified files, this book provides new perspectives of the strategic response to minority government in the 1970s, reveals a previously unrecognized distinct British tradition of minority government that goes beyond established international practice, and shows how these antecedents might apply to minority government at Westminster in 2017. This study will be invaluable to all interested in minority government and British political history, from policymakers, students, and journalists to the general public